How Early in Life do Transgender Adults Begin to Experience Gender Dysphoria? Why This Matters for Patients, Providers, and for Our Healthcare System - Michael Zaliznyak, BA; Nance Yuan, MD; Catherine Bresee, MS; Andrew Freedman, MD; Maurice M. Garcia, MD, MAS (Sexual Medicine, 2021)
ABSTRACT: Introduction: The age at which transgender women (TW) and men (TM) first experience gender dysphoria (GD) has not been reported in a U.S. population of adults seeking genital gender-affirming surgery (gGAS). Because gender is an innate part of identity, we hypothesized that untreated GD would be a part of individuals’ earliest memories. Understanding GD onset can help guide providers with when and how to focus care to patients not yet identified as “transgender Aim: (i) Determine the age at which transgender adults seeking gGAS first experience GD(ii) Determine the number of life-years that transgender adults spend living with untreated GD Methods: During initial consultation for gGAS, we asked patients the earliest age at which they experienced GD and the age at which they had their earliest episodic memory. We also queried history of anxiety, depression, and suicide attempt. Main Outcome Measures: Patients self-reported their earliest recollections of experiencing GD, earliest memories in general, and history of anxiety, depression, and suicide attempt. Results: Data from 155 TW (mean age 41.3; SD 16.3) and 55 TM (mean age 35.4; SD 10.8) were collected. Most patients (TM: 78%; TW: 73%) reported experiencing GD for the first time between ages 3 and 7 years.  For TM the mean age of onset was 6.17 years; for TW it was 6.71 years. A total of 81% of TW and 80% of TM described their first recollection of GD as one of their earliest memories. Mean years of persistent GD before the start of gender transition were 22.9 (TM) and 27.1 (TW). Rates of depression, anxiety, and suicide ideation decreased following gender transition. Conclusion: Our findings suggest that GD typically manifests in early childhood and persists untreated for many years before individuals commence gender transition. Diagnosis and early management during childhood and adolescence can improve quality of life and survival.Zaliznyak M, Yuan N, Bresee C, et al. How Early in Life do Transgender Adults Begin to Experience Gender Dysphoria? Why This Matters for Patients, Providers, and for Our Healthcare System. Sex Med 2021;9:100448.